Prediagnostic Serum Vitamin D, Vitamin D Binding Protein Isoforms, and Cancer Survival. Issue 2 (25th February 2022) - Weinstein, Stephanie J; Mondul, Alison M; Layne, Tracy M; Yu, Kai; Huang, Jiaqi; Stolzenberg-Solomon, Rachael Z; Ziegler, Regina G; Purdue, Mark P; Huang, Wen-Yi; Abnet, Christian C; Freedman, Neal D; Albanes, Demetrius
Abstract: Background: Higher circulating vitamin D has been associated with improved overall cancer survival, but data for organ-specific cancers are mixed. Methods: We examined the association between prediagnostic serum 25-hydroxyvitamin D [25(OH)D], the recognized biomarker of vitamin D status, and cancer survival in 4038 men and women diagnosed with 1 of 11 malignancies during 22 years of follow-up (median = 15.6 years) within the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Multivariable-adjusted proportional hazards regression estimated hazard ratios (HR) and 95% confidence intervals (CI) for associations between baseline 25(OH)D concentration and subsequent cancer survival; we also stratified on the common vitamin D binding protein isoforms (Gc1f, Gc1s, and Gc2) defined by two single-nucleotide polymorphisms (rs7041 and rs4588) in the vitamin D binding protein gene GC . All P values were 2-sided. Results: Higher 25(OH)D concentrations were associated with greater overall cancer survival (HR for cancer mortality = 0.83, 95% CI = 0.70 to 0.98 for highest vs lowest quintile; P trend = .05) and lung cancer survival (HR = 0.63, 95% CI = 0.44 to 0.90; P trend = .03). These associations were limited to cases expressing the Gc2 isoform (HR = 0.38 for Gc2-2, 95% CI = 0.14 to 1.05 for highest vs lowest quintile; P trend = .02; and HR = 0.30 for Gc1-2/Gc2-2 combined, 95% CI = 0.16 to 0.56; P trend < .001 for overall and lung cancer, respectively). Conclusions: Higher circulating 25(OH)D was associated with improved overall and lung cancer survival. As this was especially evident among cases with the genetically determined Gc2 isoform of vitamin D binding protein, such individuals may gain a cancer survival advantage by maintaining higher 25(OH)D blood concentrations.